PERBANDINGAN EFEKTIVITAS EDUKASI PENYAKIT HIPERTENSI MELALUI YOUTUBE SHROTS DENGAN KOMUNIKASI LANGSUNG PADA PASIEN HIPERTENSI DI PUSKESMAS X KOTA JAMBI - Ribka Pangaribuan; Deny Sutrisno; Jelly Permatasari (Jurnal Farmasi Indonesia, 2025)
Hypertension is a medical condition in which blood pressure increases significantly, which can increase the risk of cardiovascular complications. This study introduces the innovation of hypertension education through YouTube Shorts as a more effective alternative to direct communication at Puskesmas X in Jambi City. With a quantitative one group pre-test post-test design, 100 hypertensive patients were divided into two groups: 50 received education through YouTube Shorts and 50 through direct communication. Results showed YouTube Shorts was more effective in increasing knowledge (from 44.1 to 79.6) and reducing systolic and diastolic blood pressure. Direct communication also increased knowledge (from 58.08 to 75.18) and lowered systolic pressure, but was less effective in lowering diastolic pressure. The majority of participants were men aged 56-65 years, which suggests that YouTube Shorts are more effective than traditional education methods.